2017
DOI: 10.1063/1.4982357
|View full text |Cite
|
Sign up to set email alerts
|

Giant-spin nonlinear response theory of magnetic nanoparticle hyperthermia: A field dependence study

Abstract: Understanding high-field amplitude electromagnetic heat loss phenomena is of great importance, in particular in the biomedical field, since the heat-delivery treatment plans might rely on analytical models that are only valid at low field amplitudes. Here, we develop a nonlinear response model valid for single-domain nanoparticles of larger particle sizes and higher field amplitudes in comparison to linear response theory. A nonlinear magnetization expression and a generalized heat loss power equation are obta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 55 publications
(141 reference statements)
1
27
0
2
Order By: Relevance
“…According to the literature, [28] for monodisperse spherical nanoparticles one can assume that the packing of the nanoparticles in the powder configuration corresponds to a particle volume fraction close to φ = 0.64 (although the nanoparticles are not perfectly spherical or monodisperse this is considered to be a good approximation). Recall that unlike the case of the magnetic fluid in which the anisotropic axes are oriented towards the freezing field (longitudinal case [27]), in the case of the powdered sample the axes are estimated to be in the random configuration. For the colloid one can observe an increase of the effective magnetic anisotropy the higher the particle concentration.…”
Section: B Anisotropy Temperature Dependence and The Callen-callen Modelmentioning
confidence: 99%
“…According to the literature, [28] for monodisperse spherical nanoparticles one can assume that the packing of the nanoparticles in the powder configuration corresponds to a particle volume fraction close to φ = 0.64 (although the nanoparticles are not perfectly spherical or monodisperse this is considered to be a good approximation). Recall that unlike the case of the magnetic fluid in which the anisotropic axes are oriented towards the freezing field (longitudinal case [27]), in the case of the powdered sample the axes are estimated to be in the random configuration. For the colloid one can observe an increase of the effective magnetic anisotropy the higher the particle concentration.…”
Section: B Anisotropy Temperature Dependence and The Callen-callen Modelmentioning
confidence: 99%
“…Atkinson [68] identified that the biological range of AMF applications for humans should have a product of field strength and frequency less than 485 kA/mÁkHz. However, this is currently an area of debate as the value can be adjusted for coil diameter, tissue diameter, and electrical conductivity of the tissue [69][70][71]. As described by Carrião et al [70], the free current loss is proportional to the square of the distance from the coil axis and thus a better estimation for the critical field for biomedical applications can be found using the equation Hf < ð0:150=rÞ Á 485kA/mÁkHz.…”
Section: Future Directionsmentioning
confidence: 99%
“…However, this is currently an area of debate as the value can be adjusted for coil diameter, tissue diameter, and electrical conductivity of the tissue [69][70][71]. As described by Carrião et al [70], the free current loss is proportional to the square of the distance from the coil axis and thus a better estimation for the critical field for biomedical applications can be found using the equation Hf < ð0:150=rÞ Á 485kA/mÁkHz. Additionally, field conditions viable for human use could be expanded in the future as coil design is an area of active development.…”
Section: Future Directionsmentioning
confidence: 99%
“…Em geral, esse monitoramento é realizado com a Ressonância Magnética (RM) [3], que é uma técnica cara. Entretanto, tal procedimento não pode ser utilizado no caso da hipertermia magnética com nanopartículas [4][5][6][7][8][9][10], já que esta nanoterapia depende da rotação dos momentos magnéticos das nanopartículas sob ação de campo alternado. Logo, neste caso, não há como ter geração de calor pois o campo magnético de alta intensidade do ímã permanente da RM impossibilita a rotação dos momentos magnéticos das nanopartículas.…”
Section: Introductionunclassified
“…Assim, métodos baseados em sistema de processamento de sinais, simples e de baixo custo, como o sistema de imagens por ultrassom, torna-se uma alternativa interessante. Note, adicionalmente, que o ultrassom pode ser capaz de fornecer uma estimativa de temperatura interna em tempo quase real e ser combinada com várias nanoterapias térmicas, como a hipertermia magnética [4][5][6][7][8][9][10] ou a fototérmica [11].…”
Section: Introductionunclassified